ANALISIS IMPLEMENTASI BRAND AWARENESS DAN CUSTOMER RELATIONSHIP MARKETING (CRM) PADA PERBANKAN SYARIAH DI KOTA BENGKULU (Studi Pada Nasabah Bank Syariah Indonesia KCP Panorama Kota Bengkulu) - Reza Anggraini; Eka Sri Wahyuni; Aan Shar (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to analyze the influence of brand awareness and customer relationship marketing on customer purchasing decisions at BSI KCP Panorama. This research uses a qualitative method with a descriptive approach. Data collection techniques in this research used observation and interviews. This research explores customers' perceptions of a bank's brand image and how ongoing relationships built through relationship marketing influence their trust and purchasing decisions. The research results show that brand awareness plays an important role in strengthening the bank's image and increasing customer trust, while customer relationship marketing is effective in building meaningful and sustainable relationships with customers. Marketing strategies that focus on increasing brand awareness and strong relationships with customers can increase customer loyalty and purchasing decisions at BSI KCP Panorama.